Polygonatum campanulatum (Asparagaceae), a new species from Yunnan, China - Xiu-Zhen, Cai; Guang-Wan, Hu; Elizabeth Mwihaki, Kamande; Veronicah Mutele, Ngumbau; Neng, Wei (Phytotaxa, 2015)
Polygonatum Miller (1754: without pagination) is characterized by thick fleshy creeping sympodial rhizomes with elongated aerial stem and fleshy berries (Tamura et al. 1997). This genus contains 60 or more species in the world and widely distributed in the warm-temperate to boreal zones of the Northern Hemisphere with five species in Europe and three species in North America and concentrated (about 50 species) in East Asia (from Russia and Japan to Himalaya) (Tang 1978, Conran & Tamura 1998, Chen & Tamura 2000, Utech 2002, Judd 2003, Ohara et al. 2007). Chen & Tamura (2000) recognized 39 species for China, 20 of them being endemic to the country (see also Tang 1978). Since then, Floden (2014) and Zhao & He (2014) described two new taxa, both from Yunnan, China.